2019
DOI: 10.1002/lary.28216
|View full text |Cite
|
Sign up to set email alerts
|

The health utility of mild and severe dysphonia

Abstract: Objectives/Hypothesis: The impact of disease states can be measured using health state utilities, which are values that reflect economic preferences for health outcomes. Utilities for dysphonia have not been studied using direct methods. The objective of this project was to establish the baseline health utilities of mild and severe dysphonia from a societal perspective.Study Design: Direct utility elicitation survey. Methods: Four health states (monocular blindness, binocular blindness, mild dysphonia, and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Laryngeal injury and subsequent functional impairment in voice, airway, and swallowing have long been recognized as complications of prolonged intubation, regardless of the initial etiology of respiratory failure 20‐27 . These can have significant impact on health utilities and quality of life 34‐36 . Similar to prior studies about prolonged intubation, we observed patients presenting with vocal fold immobility, glottic inflammation and erythema, granulation, posterior glottic and subglottic stenosis, and posterior glottic diastasis following intubation for COVID‐19.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Laryngeal injury and subsequent functional impairment in voice, airway, and swallowing have long been recognized as complications of prolonged intubation, regardless of the initial etiology of respiratory failure 20‐27 . These can have significant impact on health utilities and quality of life 34‐36 . Similar to prior studies about prolonged intubation, we observed patients presenting with vocal fold immobility, glottic inflammation and erythema, granulation, posterior glottic and subglottic stenosis, and posterior glottic diastasis following intubation for COVID‐19.…”
Section: Discussionsupporting
confidence: 70%
“…[20][21][22][23][24][25][26][27] These can have significant impact on health utilities and quality of life. [34][35][36] Similar to prior studies about prolonged intubation, we cohort of patients presenting for laryngological evaluation -than in these prior studies. 41,42 The glottic and subglottic level sequelae of changing patient positioning from supine to prone while intubated are currently unknown, though it is reasonable to surmise this may result in further localized trauma.…”
Section: Laryngeal Complaints Physical Examination Findings and Dmentioning
confidence: 99%
“…In recent years, particular attention has been given to patient‐reported outcomes (referred to variably as PROMs or PRO measures) in clinical trial design, device development, and routine medical care . These may be general measures of quality of life (eg, SF‐36 and EQ‐5D), disease‐specific measures of utility, or other disease‐specific measure designed to capture quality of life or disability. Otolaryngology, which tends to see a large percentage of quality‐of‐life complaints particularly suited to patient‐centric assessment, has likewise had an explosion of PROMs across many different subspecialties and topics, including voice …”
Section: Discussionmentioning
confidence: 99%
“…For laryngologists treating benign and malignant conditions, voice outcomes are critical because they can significantly impact quality of life and health utility 6,7 . SILSI has been demonstrated to be safe, with few complications, 1,2,8 but its effect on voice is not well described.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For laryngologists treating benign and malignant conditions, voice outcomes are critical because they can significantly impact quality of life and health utility. 6,7 SILSI has been demonstrated to be safe, with few complications, 1,2,8 but its effect on voice is not well described. Most patients with ISGS have mild to no voice complaints, but several series suggests that there is improvement of voice-related patient-reported outcome measures after treatment of ISGS with dilation.…”
Section: Introductionmentioning
confidence: 99%